2015
DOI: 10.3747/co.22.2309
|View full text |Cite
|
Sign up to set email alerts
|

Access to Oncology Consultation in a Cancer Cohort in Northeastern Ontario

Abstract: BackgroundTo enhance cancer symptom management for residents of Sudbury–Manitoulin District, an ambulatory palliative clinic (pac) was established at the Northeast Cancer Centre of Health Sciences North. The pac is accessed from a medical or radiation oncology consultation. The primary purpose of the present population-based retrospective study was to estimate the percentage of cancer patients who died without ever having a medical or radiation oncology consultation. A secondary purpose was to determine factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Frequency of medical oncology consultation differs by cancer site and geographic region and ranges from 65% for advanced pancreatic cancer to 78% for colon cancer 12,31,32 . Only 1 other study examined the effect of income on the receipt of cancer consultation in a universal health care setting, and it found similar results 33 . Our observations are also in line with studies in private and public health systems identifying income as a barrier to chemotherapy 32,34 .…”
Section: Discussionsupporting
confidence: 85%
“…Frequency of medical oncology consultation differs by cancer site and geographic region and ranges from 65% for advanced pancreatic cancer to 78% for colon cancer 12,31,32 . Only 1 other study examined the effect of income on the receipt of cancer consultation in a universal health care setting, and it found similar results 33 . Our observations are also in line with studies in private and public health systems identifying income as a barrier to chemotherapy 32,34 .…”
Section: Discussionsupporting
confidence: 85%
“…Rural residents, however, did not demonstrate higher use of chemotherapy or ICU admissions. Some authors report that cancer patients in rural areas of Ontario are less likely to have access to cancer care resources, 17,44,45 which could contribute to rural residents being more likely to have aggressive end-of-life care. 6,7 In addition, high use of ED and hospital resources by rural residents may have occurred as a result of resource access or availability in rural areas-where EDs are being used for situations that may be addressed within ambulatory settings in urban areas.…”
Section: Main Findings Of the Studymentioning
confidence: 99%
“…10 Previously published research references inequity issues of access to resources, lengthy travel to urban centers to obtain palliative services, as well as a lack of available health care professionals and health care resources. [11][12][13][14][15][16][17] Furthermore, many rural residents often wish to receive care in their community with their families to avoid travel-related issues and costs. 18 Some additional barriers to accessing palliative care in rural areas also included lower socioeconomic status, a misunderstanding of what palliative care treatment is, and health care providers feeling ill-equipped to manage the care needs of patients nearing their end of life.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Recent findings demonstrated that rurality was one of the variables associated with lower oncology consultations in a decedent cancer cohort. 11 Furthermore, a rural geographic location was also associated with reduced access to palliative care services. 12 Of note, these studies both examined access to these health care services in Northeastern Ontario, Canada, a geographic area classified, in general, as more rural.…”
Section: Introductionmentioning
confidence: 99%
“…Health care regions in Ontario are categorized into 14 Local Health Integrated Networks (LHINs), and the North East LHIN (region 13) has a land mass that covers approximately 400,000 square kilometers, providing health care to approximately 565,000 residents (2017 estimate), with 30.2% of the population residing in rural regions. 11 , 13 , 14 When taken together the population of northern Ontario (both northeast and northwest combined) comprises approximately 6% of the total population in Ontario 11 , 12 , 13 and is characterized by less proximity to necessary health care resources, with patients usually incurring greater travel times and undertaking greater personal expenses to receive these services. 10 , 13…”
Section: Introductionmentioning
confidence: 99%